Triggers and cues that activate antibiotic production by actinomycetes. (1st February 2014) - Zhu, Hua; Sandiford, Stephanie K; van Wezel, Gilles P
Abstract: Actinomycetes are a rich source of natural products, and these mycelial bacteria produce the majority of the known antibiotics. The increasing difficulty to find new drugs via high-throughput screening has led to a decline in antibiotic research, while infectious diseases associated with multidrug resistance are spreading rapidly. Here we review new approaches and ideas that are currently being developed to increase our chances of finding novel antimicrobials, with focus on genetic, chemical, and ecological methods to elicit the expression of biosynthetic gene clusters. The genome sequencing revolution identified numerous gene clusters for natural products in actinomycetes, associated with a potentially huge reservoir of unknown molecules, and prioritizing them is a major challenge for in silico screening-based approaches. Some antibiotics are likely only expressed under very specific conditions, such as interaction with other microbes, which explains the renewed interest in soil and marine ecology. The identification of new gene clusters, as well as chemical elicitors and culturing conditions that activate their expression, should allow scientists to reinforce their efforts to find the necessary novel antimicrobial drugs.